Amyloid beta regulates ER exit sites formation through O‐GlcNAcylation triggered by disrupted calcium homeostasis. (25th October 2020) - Cho, Hyun Jin; Mook‐Jung, Inhee
Abstract : Background Information: Aberrant production of amyloid beta (Aβ) causes disruption of intracellular calcium homeostasis, a crucial factor in the pathogenesis of Alzheimer's disease. Calcium is required for the fusion and trafficking of vesicles. Previously, we demonstrated that Sec31A, a main component for coat protein complex II (COPII) vesicles at ER exit sites (ERES), is modulated by O‐GlcNAcylation. O‐GlcNAcylation, a unique and dynamic protein glycosylation process, modulates the formation of COPII vesicles. Results: In this study, we observed that disrupted calcium levels affected the formation of COPII vesicles in ERES through calcium‐triggered O‐GlcNAcylation of Sec31A. Additionally, we found that Aβ impaired ERES through Aβ‐disturbed calcium homeostasis and O‐GlcNAcylation of Sec31A in neuronal cells. Furthermore, we identified that Aβ disrupted the ribbon‐like structure of Golgi. Golgi fragmentation by Aβ was rescued by up‐regulation of O‐GlcNAcylaion levels using Thiamet G (ThiG), an O‐GlcNAcase inhibitor. Additionally, we observed that the Golgi reassembly stacking proteins having a function in Golgi stacking showed attenuation at COPII vesicles following Aβ treatment. Conclusions: This study demonstrated that Aβ impaired Sec31A targeting to ERES through altered Sec31A O‐GlcNAcylation triggered by disruption of intracellular calcium homeostasis. Significance: The findings of this study suggested that protection of ERES or Sec31 O‐GlcNAcylation may offer a promising novel avenue for development of AD therapeutics. Abstract : Research article : Golgi is critical for trafficking and modification of synthesized proteins. Amyloid‐beta, toxic molecule in Alzheimer's disease, induced Golgi fragmentation, and this event is recovered by up‐regulation of O‐GlcNAcylation of Sec31A, core component of coat protein complex II vesicle. O‐GlcNAcylation of Sec31A is associates with formation of ER exit site in our previous study. Changes in O‐GlcNAcylated Sec31A levels caused by calcium disruption by Amyloid‐beta affected on ER exit sites formation followed by protein trafficking in the protein secretory pathway.